SOIL SALINITY ASSESSMENT FOR CROP PRODUCTION SUSTAINABILITY IN JIBIA IRRIGATION SCHEME, KATSINA STATE, NIGERIA - Muazu, Abubakar; Eniolorunda, N. B.; Kabiru, S. (FUDMA JOURNAL OF SCIENCES, 2025)
Cases of soil salinity have been observed in the Jibia Irrigation Scheme (JIS), threatening sustainable crop production. This study assesses soil salinity a critical factor influencing land degradation, to develop actionable remediation strategies. Soil samples were randomly collected from the upper 0–30 cm of soil at three operational treatment areas within the project: a 3,060-hectare area served by pumping systems and a 206-hectare area served by gravity systems. Samples were analysed in the laboratory for electrical conductivity (EC) and exchangeable bases. The EC values exhibited considerable variability, ranging from 0.29 dS/m to 5.47 dS/m, which reflects significant differences in soil salinity across the sites. Laboratory analyses revealed exceptionally high concentrations of exchangeable sodium (Na+) relative to other essential bases; calcium (Ca2+), magnesium (Mg2+), and potassium (K+). The percent base saturation (PBS) values further highlighted deficiencies: potassium ranged from 1.37% to 11.50%, magnesium from 1.46% to 6.70%, calcium from 13.90% to 36.46%, and sodium dominated at 45.56% to 76.62%. These imbalances in soil nutrient levels impair crop yields and quality, exacerbating economic losses and food insecurity in the scheme area. The study recommends implementing a series of remediation strategies to restore the productivity of the degraded farmlands. These strategies include soil leveling or grading, application of gypsum or calcium chloride to ameliorate salinity, and crop production practices that are tolerant to sodium. This study presents a thorough assessment of the effects of soil salinity in the JIS and practical recommendations to enhance soil health and support sustainable agricultural practices in the...